Characterization of the Flexural Properties of Polyester Matrix Composites Reinforced with Continuous Jute Fibers - Sergio N. Monteiro (The Minerals, Metals and Materials Society, 2010)
Jute fiber reinforced polymer composites are among the most investigated and applied natural composites. In this past decade the mechanical properties of these composites has been assessed for various types of test conditions. However, the reported results correspond mainly to short-cut jute fiber composites, which do not present the highest mechanical strength as compared to continuous fibers of the same kind. In order to complement these results, the present work evaluated the mechanical behavior, by means of flexural tests, of polyester matrix composites reinforced with continuous jute fibers. Bend tests were conducted in standard specimens with up to 40% of jute. Fracture analysis by SEM displayed the rupture mechanisms. The results showed an improvement in some flexural properties with incorporation of jute fiber. However, a low fiber/matrix interfacial stress was responsible for limitation in the values attained by some properties.